Pengaruh pelatihan tenaga gizi puskesmas terhadap program keluarga sadar gizi di Kota Samarinda Provinsi Kalimantan Timur - Sri Sedono Iswandi; Endy Paryanto Prawirohartono; Abidillah Mursyid (Jurnal Gizi Klinik Indonesia, 2007)
Background: Under nutrition remains a major malnutrition problem in Indonesia. In dealing with the problem, the Indonesian government has already implemented strategies including empowering health workers and families. It is very likely that the nutrition problem and the family awareness on nutrition are closely related. Families that practice balanced nutrition are able to recognize and cope with their nutrition problems are defined as nutritionally aware or better known as Kadarzi.Objective: To study the impact of nutrition training on family awareness on nutrition in Samarinda province of East Kalimantan.Method: This observational study was carried out using cross-sectional design. The study population was household with under five years old children in Samarinda. A hundred and thirty two households were drawn from the population with cluster random sampling technique. The data gathered in the study were Kadarzi indicators, achievement program on Kadarzi, and related information that was collected by inter-viewing Head of Primary Health Care Center (puskesmas) and Integrated Health Service Center (posyandu) cadres at the village level.Result: The training on nutrition had an effect to attainment of the family awareness (Kadarzi) in Samarinda (OR=6,9; 95 % CI =1,98 – 23,82). Other variable which playing a part in of the influence was mother education.Conclusion: Nutrition staff who were well trained had an effect to attainment of the family awareness.